STUDI PEMIKIRAN ASGHAR ALI ENGINEER TENTANG NAFKAH ISTRI PASCA IDDAH (Eksistensi Urf Dalam Kompilasi Hukum Islam) - Musa Arifin (Institut agama islam negeri Padangsidimpuan, 2015)
When a dissolutuion on marriage happened between a married couple, there are some obligations wich must be obeyed by the spouses and one of the obligations is the man requesting the divorce is obligated to give a living to the divorce women. the living is accordance with the economic atatus of the man (husband) (Based on the capability), the living is as a kind of long as the divorced woman in ‘iddah.